2015
DOI: 10.1586/14760584.2016.1106942
|View full text |Cite
|
Sign up to set email alerts
|

Self-disseminating vaccines for emerging infectious diseases

Abstract: Modern human activity fueled by economic development is profoundly altering our relationship with microorganisms. This altered interaction with microbes is believed to be the major driving force behind the increased rate of emerging infectious diseases from animals. The spate of recent infectious disease outbreaks, including Ebola virus disease and Middle East respiratory syndrome, emphasize the need for development of new innovative tools to manage these emerging diseases. Disseminating vaccines are one such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 62 publications
1
57
0
Order By: Relevance
“…The potential for a transmissible or self-disseminating vaccine to facilitate efforts to control and eradicate infectious disease has long been appreciated [42], but the oral polio vaccine and vaccines designed for wildlife remain the only welldocumented examples [1,6,[8][9][10][11][12]. Much of the reticence surrounding the development of transmissible vaccines stems from the justifiable concern that the potential for evolutionary reversion to wild-type virulence outweighs their potential benefits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential for a transmissible or self-disseminating vaccine to facilitate efforts to control and eradicate infectious disease has long been appreciated [42], but the oral polio vaccine and vaccines designed for wildlife remain the only welldocumented examples [1,6,[8][9][10][11][12]. Much of the reticence surrounding the development of transmissible vaccines stems from the justifiable concern that the potential for evolutionary reversion to wild-type virulence outweighs their potential benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the real power of transmissible vaccines likely lies in their ability to improve vaccine coverage in populations of livestock and wildlife where direct vaccination of a significant proportion of the population is excessively costly or even impossible in many cases. Although transmissible vaccines have not yet been used in this capacity on a large scale, a recombinant transmissible vaccine has been developed to protect wild rabbit populations against myxomatosis [9] and to interrupt the transmission of Sin Nombre hantavirus in reservoir populations of deer mice [6]. Similar approaches could be used to develop transmissible vaccines against invasive wildlife diseases, such as West Nile virus [27], to protect threatened wildlife populations from infectious disease [28] or to eliminate diseases like rabies from wild reservoir populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the choice of a vector may be based on considerations that lie outside model results, and the model results will then inform the possibilities and avenues for success. Consider cytomegalovirus (CMV), a vector currently being used in the development of transmissible vaccines targeting Ebola and Lassa fever (Marzi et al, ; Murphy et al, ; Tsuda et al, , ). CMV appears promising because of its high level of species specificity, and ability to readily reinfect previously infected hosts (Murphy et al, ), a property shown to be critically important here, and in a previous study (Basinski et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases where culling has been employed and studied, however, it has been shown to have potentially counter-intuitive impacts, potentially increasing the prevalence of the target pathogen (Streicker et al 2012; Amman et al 2014). A second alternative to conventional vaccination relies on the use of transmissible vaccines capable of transmitting infectiously within the target population (Murphy et al 2016; Nuismer et al 2016; Bull et al 2018). Transmissible vaccines have been show to substantially improve the likelihood of eliminating infectious disease in theoretical studies, but have been explored empirically in only a small number of cases (Bárcena et al 2000; Angulo and Barcena 2007; Murphy et al 2016; Bull et al 2018).…”
Section: Discussionmentioning
confidence: 99%